Enabling transfer of learning. Case Wärtsilä Services’ Sales Accelerator workshop. - Kuusisto, Johanna (My University, 2014)
The goal of this study is to identify the enabling factors that ensure the transfer of learn-ing after the training and what are the actions that need to be taken in order to set foun-dation for the transfer of learning in three stages: before, during and after the training. The case study used in this research is Wärtsilä Services Sales Accelerator workshop which whole learning process from the need analysis until evaluation is analyzed based on the theory presented in the study. The theoretical framework of the study covers the role of Learning and Development in the core business change programs, training as a competence development method, adult as a learner and the study’s key concept: trans-fer of learning. Theory continues to different models to plan the training from the be-ginning until the end, in evaluating the training. Finally two evaluation models are pre-sented. The study is conducted as empirical and qualitative case study that also used quantita-tive methods in analyzing the data. The aim is to identify how transfer of learning was supported, if it happened and what was the outcome in Sales Accelerator workshops arranged in 2013. In the empirical part documented knowledge was used and two struc-tured surveys were conducted in two different phases: immediately after the workshop and 3-10 months after the sample participated in the workshop. The sample for the both surveys was all the employees who participated in Sales Accelerator workshop in 2013. The findings and analysis of the empirical data confirms the theory that transfer of learning needs to be planned; it needs to part of the training planning process, it should have a focus on before, during and after the training phases and it happens in case there is positive motivation and expectations cascading down from the environment, manager and from the individual itself. In case work environment and manager’s support and the expectations are not in place it will decrease the likelihood to transfer the training con-tent into permanent learning and visible change in behavior which is resulting on the business results finally.
Keywords: Training; transfer of learning; learning process; evaluation of training; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Henkilöstöjohtamisen maisteriohjelma|en=Master's Programme in Human Resource Managment|